From lithium to potassium: Comparison of cations in poly(ethylene oxide)-based block copolymer electrolytes for solid-state alkali metal batteries. (20th June 2023) - Khudyshkina, Anna D.; Butzelaar, Andreas J.; Guo, Yiran; Hoffmann, Maxi; Bergfeldt, Thomas; Schaller, Mareen; Indris, Sylvio; Wilhelm, Manfred; Théato, Patrick; Jeschull, Fabian
Highlights: Comparative characterization of SPEs with ATFSI ( A = Li, Na and K) is provided. Microphase-separated copolymer with polystyrene block yields a rigid polymer matrix. Total ionic conductivities in Li-, Na- and K-SPEs approached similar values. Reliable transference numbers ( T A + ) are difficult to quantify for Na- and KTFSI-SPEs. KTFSI-SPE retains 94% of capacity over 100 cycles in K-metal/SPE/cathode cell. Abstract: Liquid electrolytes (LEs) commonly show severe side reactions at the electrode-electrolyte interface, especially with alkali metal anodes, leading to rapid capacity fade of metal-ion batteries. Solid polymer electrolytes (SPEs), however, contribute to the suppression of side reactions due to their inherent inertness and high mechanical strength, providing long-term stable battery operation. Herein, we investigated physical and electrochemical properties of SPEs based on our previously reported microphase-separated poly(vinyl benzyl methoxy poly(ethylene oxide) ether)- block -polystyrene block copolymer (PVBmPEO- b -PS) with different alkali metal ions ( A + = Li +, Na + or K + ) and their use in the respective metal batteries, showing the potential for the transition from lithium to post-lithium batteries. Rheological and thermal properties as well as ion transport in the SPEs with different bis(trifluoromethanesulfonyl)imide (TFSI) salts concentrations revealed similar shear storage moduli (G') for the investigated SPEs, while the lowest glass transition temperatures ( T g ) were found for KTFSI-based films. By contrast, the highest total ionic conductivity was found for the LiTFSI-based SPEs. To quantify the A + transference numbers ( T A + ), the Bruce-Vincent method and pulsed-field gradient (PFG) NMR were conducted, revealing significant challenges for T A + determination of post-Li systems. Further, the examination of the interfacial stability of SPE/A interfaces by conducting plating/stripping experiments revealed significantly higher resistances for sodium- and potassium-based systems in comparison to their lithium-based counterpart. Nonetheless, A-metal/SPE/cathode cells with PVBmPEO- b -PS-based Na- and K-SPEs with the Prussian Blue analogues (PBAs, Na2- x Fe[Fe(CN)6 ] and K2- x Fe[F e (CN)6 ]) positive electrodes and the respective alkali metal negative electrodes enabled cycling at elevated temperature of 55 °C. Herein, both sodium and potassium metal batteries exhibited stable cycling with capacity retentions of 73% over 100 cycles for the Na-cell, and 94% over the same cycle number for the K-cell, (and a high coulombic efficiency (CE) of 98% at the 100th cycle). Graphical abstract: Image, graphical abstract